OPTICOR CREATE METHODOLOGIES TO RAlSE THE REGIONAL COMPETITlVENESS: THE MEfHODOLOGY SIIC, APPUED TO THE CHAIN OF LEATHER, SHOES AND LEATHER GOODS. - Caicedo Asprilla, Henry; Gonzalez Campo, Carlos Heman; Castro Díaz, Aracely (Cuadernos de Administración, 2008)
This document presents the methodology of  intervention JICS, InstitutionaJ Innovation and Competitive Systems, developed by the Observatory of Industrial Techno\ogical Foresight OPTTCOR. The object of analysis of the methodology are organizations such asenterprises, productive sectors and regions, to the extent that these can be considered like organized systems that share standards, scientific, material and human resources, which compete for improving the life qua lit y of its members. The OPTICOR validated the methodology IlCS, through a study called "Collective Building of regionals competitives strategies fortakng advantage ofthe opportunities in globalization ofmarkets from chain ofleather,shoes and leather goods". In this project was implemented the different phases of the methodology; Competitive referencing, economic intelligence, definitíon of scenarios, prioritization of projects, and was raised two needs, making the sector a conglomerate and design a strategy for knowledge management, the application of the methodology required of 10 months, conducting 8 workshops, the participation of 90 businessmen and 43 institutions of sectoral support.